TINGKAT KEKRITISAN LAHAN DI SUB DAS TEBING SIRING DAS TABUNIO KABUPATEN TANAH LAUT - Laila Indasari; Syarifuddin Kadir; Eko Rini Indriyatie (Universitas Lambung Mangkurat, 2023)
Critical land is supported by the physical condition of the soil which is prone to erosion due to excessive land use, high rainfall and steep slope conditions. The Tebing Siring Sub-Watershed is one of the upstream parts of the Tabunio watershed which is dominated by plantations due to the large number of activities of residents managing land such as plantations. This study aims to analyze the level of land criticality and determine efforts to control the level of land criticality in the Tebing Siring Sub-Watershed of the Tabunio Watershed, Tanah Laut Regency. The methods used in the study are overlapping (overlayed) methods of land cover maps, slope maps and soil type maps with critical land determinant parameters in agricultural business cultivation areas including productivity, slopes, erosion and management. The results showed that land cover/use in oil palm plantations is included in the critical potential category, rubber plantations are in the rather critical to critical category, reeds are included in the critical category and open land is included in the very critical category. Factors caused by the slope of the slope, soil factors, the degree of danger of erosion and its vegetation. Efforts to control the level of land criticality through forest and land rehabilitation directives. Oil palm and rubber plantations are maintained and improved maintenance but with an intercropping pattern and rehabilitated with superior plant types and steep marbles directed at making terraces. Open land and reeds are converted into forests through enrichment of forest plants and Multy Purpose Tree Species (MPTS) that correspond to the place of growth according to plant species and land productivity can increaseLahan kritis didukung oleh kondisi fisik tanah yang rentan terjadi erosi akibat penggunaan lahan yang berlebihan, tingginya curah hujan dan keadaan lereng curam. Sub DAS Tebing Siring salah satu bagian hulu dari DAS Tabunio yang didominasi oleh perkebunan karena banyaknya aktifitas penduduk mengelola lahan seperti perkebunan. Penelitian ini bertujuan untuk menganalisis tingkat kekritisan lahan dan menentukan upaya pengendalian tingkat kekritisan lahan pada Sub DAS Tebing Siring DAS Tabunio Kabupaten Tanah Laut. Metode yang digunakan pada penelitian adalah metode tumpang tindih (di-overlay) peta tutupan lahan, peta lereng dan peta jenis tanah dengan parameter penentu lahan kritis pada kawasan budidaya usaha pertanian meliputi produktivitas, lereng, erosi dan manajemen. Hasil yang diperoleh menunjukkan bahwa penutupan/penggunaan lahan pada perkebunan sawit termasuk kategori potensial kritis, perkebunan karet termasuk kategori agak kritis hingga kritis, alang-alang termasuk kategori kritis serta lahan terbuka termasuk kategori sangat kritis. Faktor-faktor yang disebabkan oleh kemiringan lereng, faktor tanah, tingkat bahaya erosi dan vegetasinya. Upaya pengendalian tingkat kekritisan lahan melalui arahan rehabilitasi hutan dan lahan. Perkebunan sawit dan karet yaitu tetap dipertahankan dan ditingkatkan pemeliharaannya namun dengan pola tumpangsari serta direhabilitasi dengan jenis tanaman yang unggul dan pada kelerengan yang curam diarahkan membuat terasering. Lahan terbuka dan alang-alang dikonversi menjadi hutan melalui pengkayaan tanaman hutan dan Multy Purpose Tree Species (MPTS) yang sesuai dengan tempat tumbuh sesuai spesies tanaman serta produktivitas lahan dapat meningkat.